Plastic Waste Reduction Policy Model based on Sustainable Development Principles in Sultan Ageng Tirtayasa University - Ferina Ardhi Cahyani; Nurikah Nurikah (Nurani Hukum, 2022)
Plastic is a part of human life. Plastic packaging dominates the packaging market share in the world, replacing cans and glass packaging. Plastic is used because it is an inexpensive material, not easily weathered, lightweight, and anti-rust. Human activities cannot be separated from the use of plastics, but the increasing use of plastic results in increased pollution of land and even oceans. This also certainly affects the world's ecosystem. Because of the dangers of plastic for the environment, the government has begun to aggressively create programs and policies aimed at educating the public about the impact of plastic consumption and its dangers on the environment. It also aims to change people's culture of using single-use plastics. Not only the government, but at the university policy level it is also necessary to make policies regarding the restrictions on the use of single-use plastics. This study uses an empirical juridical research method that uses a juridical approach by analyzing primary data in the form of interviews and secondary data derived from primary legal materials. The purpose of this study was to determine the policy of reducing single-use plastic waste in the Sultan Ageng Tirtayasa University environment. These policies will be reviewed based on the principles of sustainable development or sustainable development which balances four aspects, namely economic, social, environment and law aspects